Study on the composition characteristics of the intestinal microbiota in three species of cranes under captive conditions - Gao, Xiaodong; Dong, Yuehuan; Li, Nannan; Wen, Feng; Shang, Shuai; Wu, Qingming; Zhang, Honghai (Frontiers in Ecology and Evolution, 2026)
Cranes are globally threatened yet understudied in terms of their gut microbiome, which is crucial for their health in captivity. This study examines the gut microbiota composition of three captive crane species using 16S rRNA gene sequencing of fecal samples. The research addresses the critical role of gut microbiota in nutrient metabolism, immune regulation, and environmental adaptation, particularly under captive conditions where dietary shifts may disrupt microbial balance. Fecal samples from 45 juvenile cranes were collected, and genomic DNA was extracted for 16S rRNA gene sequencing. Bioinformatic tools were used to analyze microbial diversity, composition, and functional pathways. Significant interspecific differences were observed. The common crane’s microbiota was dominated by Bacillota (93.05%), enhancing cellulose degradation, while the Demoiselle Crane exhibited higher diversity with Pseudomonadota (21.95%) and Fusobacteriota (2.83%), reflecting omnivorous adaptations. The Red-crowned Crane showed intermediate Bacillota (78.32%) and notable Plesiomonas (12.48%), linked to aquatic diets. Alpha diversity was lowest in Demoiselle Cranes, and beta diversity revealed pronounced structural divergence. Functional analysis identified species-specific adaptations, such as alcohol detoxification in wetland cranes and pyruvate fermentation in arid-adapted Demoiselle Cranes. Captivity influences crane microbiota composition, with interspecific differences driven by evolutionary dietary specialization. The findings underscore the need for tailored dietary management in conservation programs to maintain microbial health and host adaptability. This study provides a scientific basis for optimizing captive crane care and supporting biodiversity conservation efforts.